Testing a Middle -Range Theory of Heart Failure Self-Care. (October 2021) - Attaallah, Sumayya A.; Peters, Rosalind M.; Benkert, Ramona; Yarandi, Hossein; Oliver-McNeil, Sandra; Hopp, Faith
A middle-range theory of heart failure self-care, derived from the self-care deficit theory of nursing, was tested among 175 Arab American older adults with heart failure. The middle-range theory achieved good statistical fit, but not all hypothesized relationships were supported. Specifically, conceptualizing basic conditioning factors as a single latent variable was not supported. However, individual factors of depression, social support, and time living with heart failure had a direct effect on both self-care agency and quality of life. Understanding predictors and outcomes of self-care within a theoretical framework is essential in caring for patients with heart failure.